Application of the Daqu Rule Method to Improve the Quality of Al-Qur’an Reading of Students at the Tahfizh Daarul Qur’an Tegineneng Pesawaran Islamic Boarding School - Rahman, Akbar; Fajri, M. Rizkal; Rohili, Tahir (Civiliza Publishing, 2024)
The approach is very crucial in determining the success of learning to read the Qur’an when implementing the process. Various approaches to reading the Qur’an have been widely used, such as the Al-Baghdadi technique, Iqro’, An Nahdiyyah, Jibril, Qiro’ati, Ummul Quro’, Ummi, Yanbu’a, and the Kaidah Daqu method. The problem of first-year students at the Tahfizh Daarul Qur’an Tegineneng Pesawaran Islamic Boarding School still not being able to read the Qur’an according to the rules of tajwid and tartil, this is the driving factor for this study. Finding out how Daarul Qur’an uses the Kaidah Daqu Method to improve students’ reading of the Qur’an is the main objective of this study. By using a descriptive research strategy based on qualitative data, this study attempts to provide a factual, methodical, and field-based picture of the situation. Interviews, observations, and documentation are the methods used to collect data. After ensuring that the data was authentic and reliable, we used qualitative analysis to see how well the Quran reading was done. The study found that students’ Quran reading comprehension improved. The progress achieved each month clearly shows this